On the stationary vibrations of a rectangular plate subjected to stress prescribed partially at the circumference - M. G. El Sheikh; A. H. Khater; D. K. Callebaut (International Journal of Mathematics and Mathematical Sciences)
The stationary periodical problem of a vibrating rectangular plate, stressed at a segment while fixed elsewhere at one of its edges, is considered. Using the finite Fourier transformation, the problem is converted to a singular integral equation that in turn can be reduced to an infinite system of algebraic equations. The truncation of the algebraic system is justified.